'I became a Taiwanese after I left Taiwan': identity shift among young immigrants in the United States. Issue 2 (4th March 2023) - Ho, Ming-sho; Li, Yao-Tai
ABSTRACT: Migration and transnationalism studies use variables such as migration trajectory, length of stay, and ties with origin country to examine migrant identities. Research has also found that contrary to the prediction of assimilation theory, some well-adapted migrants activate their origin country identities. Using young Taiwanese immigrants who stayed in Taiwan for most of their lives and went to the United States as a case, this article examines the mechanisms of context- and event-driven identity shift. We argue that these young adult Taiwanese immigrants – most of whom are first-generation – find that they are situated in a context where they have to 'choose' and 'perform' an identity for everyday interaction. Negative experiences with Chinese immigrants and the realization of Taiwan's marginality encouraged them to activate their homeland (Taiwan) identity. This article contributes to migration and identity literature by analysing the consequences (identity triggers and shifts) of everyday encounters and events in an immigration setting.